Directions for Research on Climate and Conflict. Issue 7 (3rd July 2020) - Mach, Katharine J.; Adger, W. Neil; Buhaug, Halvard; Burke, Marshall; Fearon, James D.; Field, Christopher B.; Hendrix, Cullen S.; Kraan, Caroline M.; Maystadt, Jean‐Francois; O'Loughlin, John; Roessler, Philip; Scheffran, Jürgen; et al.
Abstract: The potential links between climate and conflict are well studied, yet disagreement about the specific mechanisms and their significance for societies persists. Here, we build on assessment of the relationship between climate and organized armed conflict to define crosscutting priorities for future directions of research. They include (1) deepening insight into climate‐conflict linkages and conditions under which they manifest, (2) ambitiously integrating research designs, (3) systematically exploring future risks and response options, responsive to ongoing decision‐making, and (4) evaluating the effectiveness of interventions to manage climate‐conflict links. The implications of this expanding scientific domain unfold in real time. Key Points: Disagreement about the relationship between climate and the risk of violent conflict persists, limiting societal management of the risks Future directions for climate‐conflict research include deepening insight on what the links are, when they matter, and how they manifest Compelling opportunities necessitate integrating research designs, responsive to ongoing decision‐making and potential responses